2016
DOI: 10.1186/s12885-016-2911-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of optical coherence micro-elastography as a method to visualize micro-architecture in human axillary lymph nodes

Abstract: BackgroundEvaluation of lymph node involvement is an important factor in detecting metastasis and deciding whether to perform axillary lymph node dissection (ALND) in breast cancer surgery. As ALND is associated with potentially severe long term morbidity, the accuracy of lymph node assessment is imperative in avoiding unnecessary ALND. The mechanical properties of malignant lymph nodes are often distinct from those of normal nodes. A method to image the micro-scale mechanical properties of lymph nodes could, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Several studies have demonstrated that OCE can visualize tumor in excised human breast tissue [18,[23][24][25][26]. Eventually, OCE may provide intraoperative feedback to surgeons to assist in the detection of tumor, which may reduce the number of re-excision surgeries required to remove residual tumor missed during the initial surgery.…”
Section: Ex Vivo Malignant Breast Tumormentioning
confidence: 99%
“…Several studies have demonstrated that OCE can visualize tumor in excised human breast tissue [18,[23][24][25][26]. Eventually, OCE may provide intraoperative feedback to surgeons to assist in the detection of tumor, which may reduce the number of re-excision surgeries required to remove residual tumor missed during the initial surgery.…”
Section: Ex Vivo Malignant Breast Tumormentioning
confidence: 99%
“…However, contrast of such imaging often is insufficient for precise diagnostics of metastases in LNs. Presently, for enhancing the contrast of metastatic LN detection, structural OCT imaging was supplemented with such OCT modalities as attenuation imaging [30] and OCE [31]. Among new OCT modalities, intraoperatively feasible OCE has the high potential to assess LN architecture without physical resection of LNs for analysis, which provides the surgeon with valuable and accurate real-time information on the presence/absence of metastatic disease and potentially enables the preservation of reactive but non-metastatic LNs, thus reducing the risk of lymphedema.…”
Section: Introductionmentioning
confidence: 99%
“…The microscopic displacement visualizes the mechanical properties of the tissue [35], while more quantitative elastographic information, such as the Young's modulus [31] or shear modulus [36], can be obtained by combining the displacement information with the mechanical stimulation information. OCE has been used to investigate the mechanical properties of cornea [37], breast cancer tissue [38], and several other tissues [39][40][41][42]. The combined use of OCE and PS-OCT has also been demonstrated [43].…”
Section: Introductionmentioning
confidence: 99%